A Cephalometric Evaluation of Anterior Cranial Base Slope in Patients with Different Skeletal Malocclusions - Rehman, Haseeb ur; Abid, Amra Minhas; Ahmed, Zainab; Aiza Bint e Shafqat,; Ali Khan, Anas; Yahya Obied, Bassam Hamoud; Ahmed Mahdi, Ibrahim Magdi; Mohamed, Ahmed Elawady; Hassan, Muhammad Ali (Indus Journal of Bioscience Research, 2024)
Objective: To assess the correlation in the anterior cranial base (SNA, SNB angles) and among the three different skeletal malocclusions. Study Design: Descriptive cross-sectional study. Study setting: Orthodontic Department KRL Hospital G-9, Islamabad, from March to August 2024. Methodology: The data included lateral cephalograms of people undergoing orthodontic treatment. By simple consecutive non-random sampling technique, a total sample size of 120 patients was selected. IBM SPSS version 23.0 was used for the data analysis. Quantitative data like age, SNA, SNB and ACB slope was expressed in mean (SD) as descriptive statistics. Pearson correlation coefficient was used to evaluate the relationship between the anterior cranial base and the skeletal malocclusions. A p-value ≤ 0.05 was considered statistically significant. Results: Out of 120 patients evaluated in this study, the distribution across the three skeletal malocclusions was as follows: 10% were classified as skeletal class I, 65% as skeletal class II, and 25% as skeletal class III. A significant correlation was observed between the anterior cranial base slope and the type of skeletal malocclusion (p < 0.05). The patients with Class II malocclusion, the SNA angle was notably higher while in Class III malocclusion patients, the SNB angle was significantly increased. Additionally, the SN-FH angle demonstrated a steeper slope in Class III patients compared to those with Class I and Class II malocclusions. There was no significant difference in anterior cranial base length (BA-S) across the malocclusion groups. The correlation analysis between SNA, SNB, and the anterior cranial base slope indicated that the steepness of the cranial base plays a role in the manifestation of the skeletal malocclusions. Conclusion: This research study underscores the significance of the anterior cranial base in the development of skeletal malocclusions. The findings suggest that patients with Class II malocclusion exhibit a steeper anterior cranial base slope, whereas Class III patients tend to have a flatter cranial base slope. These variations in anterior cranial base morphology can serve as effective diagnostic tools in the assessment, evaluation, and treatment planning of skeletal malocclusions. The study also highlights the complex interplay between cranial base morphology and skeletal relationships, indicating the need for comprehensive analysis in orthodontic assessment and treatment strategies.